2018
DOI: 10.11591/ijere.v1i1.10980
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pre-Service Music Teachers Towards Value Education In Turkey

Abstract: <p>In the music education curriculum, which is implemented from 2017-2018 academic year, the directive for teaching values was prepared for the first time. In this context, the research was conducted by comparing the attitudes of pre-service music teachers towards values education in terms of some variables, which will be included in the courses of value education according to the new music education curriculum. Data collected using the values education attitude scale were analysed using t-test, Kruskal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The study found that the teachers' attitudes toward values education did not differ significantly in relation to gender. There are research findings in the literature indicating that the views or attitudes of teachers and teacher candidates toward values education do not differ based on gender (Eğilmez, Eğilmez, & Engür, 2018;Baş, Taşkıran, & Bulut, 2016;Can, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the teachers' attitudes toward values education did not differ significantly in relation to gender. There are research findings in the literature indicating that the views or attitudes of teachers and teacher candidates toward values education do not differ based on gender (Eğilmez, Eğilmez, & Engür, 2018;Baş, Taşkıran, & Bulut, 2016;Can, 2008).…”
Section: Discussionmentioning
confidence: 99%